2020
DOI: 10.3390/ma13225231
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CVD- and PVD-Coated Carbides and PVD-Coated Cermet Inserts in the Optimization of Surface Roughness in Turning of AISI 1045 Steel

Abstract: In this study, an experimental and statistic investigation approach based on analysis of variance (ANOVA) and response surface methodology (RSM) techniques was performed to find the significant main effects and two-factor interaction effects and to determine how the controllable factors such as cutting speed, feed rate, depth of cut (DOC), tool nose radius, substrate and coating method of cutting tools influence surface quality in turning of AISI 1045 steel. The first optimal or near-optimal conditions for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The use of trial-and-error is one of the options available to optimize the associated parameters, but this approach is not suitable for current industries using complex manufacturing processes, as it is time-consuming and costly [ 3 ]. Therefore, applying optimisation methods such as the Response Surface Methodology (RSM), Genetic Algorithm (GA), Particle Swarm Optimisation (PSO) and Taguchi is a good option to optimise the setting of processing parameters to mould parts with better quality [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of trial-and-error is one of the options available to optimize the associated parameters, but this approach is not suitable for current industries using complex manufacturing processes, as it is time-consuming and costly [ 3 ]. Therefore, applying optimisation methods such as the Response Surface Methodology (RSM), Genetic Algorithm (GA), Particle Swarm Optimisation (PSO) and Taguchi is a good option to optimise the setting of processing parameters to mould parts with better quality [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…RSM is among the optimisation methods that have been used by many researchers [ 6 , 7 , 8 , 9 , 10 ]. Sudsawat and Sriseubsai [ 10 ] conducted research using the RSM optimisation approach to create optimal process settings to minimise warpage and volume shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that increased feed results in increased surface roughness, while increasing the cutting speed slightly improves the surface quality. Paese et al [23] performed an experimental investigation based on ANOVA and RSM techniques to determine how the factors such as cutting speed, feed, depth of cut, corner radius, substrate and coating method influence surface quality. The PVD-coated inserts in combination with lower feed and higher corner radius generated the lowest surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Paese et al [8] evaluated the performance of CVD, PVD, and cermet inserts after turning the AISI 1045 carbons steel shaft by using ANOVA analysis and response surface methodology. The cermet and PVD coated inserts generated minimum surface roughness compared with the CVD insert.…”
Section: Introductionmentioning
confidence: 99%